Seychelles : Assessment Letter for the African Development Bank. (Policy Papers; Policy Paper ;, 2009)
Macroeconomic performance of Seychelles under the Stand-by Arrangement (SBA) has been favorable and the reforms continue to be pursued with a high degree of ownership and broad public support. The liberalization of the exchange regime, a strong fiscal adjustment, and prudent monetary policies have contributed to restoring macroeconomic stability. Program implementation has been exemplary and talks to restructure public external debt are progressing well. A debt restructuring agreement with commercial creditors, on terms comparable to those agreed with Paris Club creditors, is a crucial element in reestablishing a sustainable public debt outlook and supporting economic recovery.